2010
DOI: 10.1111/j.1600-0447.2009.01439.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychotic‐like experiences are associated with suicidal feelings and deliberate self‐harm behaviors in adolescents aged 12–15 years

Abstract: Psychotic-like experiences are associated with suicidal feelings and deliberate self-harm behaviors in adolescents aged 12-15 years.Objective: Psychotic disorders are a significant risk factor for suicide, especially among young people. Psychotic-like experiences (PLEs) in the general population may share an etiological background with psychotic disorders. Therefore, the present study examined the association between PLEs and risk of suicide in a community sample of adolescents. Method: Psychotic-like experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
95
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(110 citation statements)
references
References 37 publications
14
95
0
Order By: Relevance
“…There was no statistically significant difference between the sexes in this association. The prevalences of current suicidal ideation and acts of self-harm reported in the present study were comparable with those presented in our previous study in a community sample of younger adolescents (Nishida et al 2010).…”
Section: Discussionsupporting
confidence: 91%
“…There was no statistically significant difference between the sexes in this association. The prevalences of current suicidal ideation and acts of self-harm reported in the present study were comparable with those presented in our previous study in a community sample of younger adolescents (Nishida et al 2010).…”
Section: Discussionsupporting
confidence: 91%
“…First, the association between PE and suicidal ideation and behaviour has been investigated mostly in cross-sectional studies (Capra et al, 2015;DeVylder et al, 2015b;Jang et al, 2014;Kelleher et al, 2012c;Nishida et al, 2010;Saha et al, 2011;Temmingh et al, 2011), disabling causal inferences. Second, several studies included psychiatric diagnoses in the regression models to control for confounding (Calkins et al, 2014;DeVylder et al, 2015b;Fisher et al, 2013;Koyanagi et al, 2015;LewisFernandez et al, 2009;Olfson et al, 2002;Saha et al, 2011;Sharifi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In population-based research, 2 recent questionnaire surveys have linked psychotic symptoms and suicidal behavior. Nishida et al 25 found that adolescents who endorsed a questionnaire item about hallucinations were 3 times more likely to also endorse an item related to suicidal ideation. Saha et al, 26 on the other hand, found that individuals who endorsed questionnaire items about delusions were 2 to 4 times more likely to endorse questionnaire items on suicidal behavior.…”
mentioning
confidence: 99%